2013
DOI: 10.1080/09540121.2012.752564
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of a study using a standardized locally procured macronutrient supplement as adjunctive therapy to HIV treatment in Kenya

Abstract: Poor nutritional status at initiation of antiretroviral therapy (ART) is predictive of mortality. Decreased dietary intake is a major determinant of weight loss in HIV. Despite a biological rationale to treat undernutrition in adults receiving ART, few studies have provided data on feasibility, safety, effectiveness, and sustainability of specific macronutrient supplements with HIV treatment in adults, especially supplements such as a food basket, a supplement approach seldom evaluated in spite of its wide use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Increasing prices of food and decreased food intake are of particular importance in HIV infection, especially in poor countries [56,61]. Increasing prices of food and decreased food intake are of particular importance in HIV infection, especially in poor countries [56,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing prices of food and decreased food intake are of particular importance in HIV infection, especially in poor countries [56,61]. Increasing prices of food and decreased food intake are of particular importance in HIV infection, especially in poor countries [56,61].…”
Section: Discussionmentioning
confidence: 99%
“…Immunostimulating properties of vitamins, particularly vitamins B, A, E, and C, as well as microelements-selenium, zinc, and iron-were confirmed in clinical trials and it was demonstrated that their intake reduces the risk of developing full-blown AIDS [56]. Immunostimulating properties of vitamins, particularly vitamins B, A, E, and C, as well as microelements-selenium, zinc, and iron-were confirmed in clinical trials and it was demonstrated that their intake reduces the risk of developing full-blown AIDS [56].…”
Section: Vitamins and Mineralsmentioning
confidence: 94%
“…Local food procurement was strongly linked to promoting social sustainability in the reviewed articles. Procuring local food was often associated with providing healthy and nutritious food, see e.g., [40,72,84]. Local food was also regarded as an assurance of quality and transparency, leading to consumers' trust and food security, see, e.g., [39,58,67,82,85,86].…”
Section: Framing Social Sustainabilitymentioning
confidence: 99%